A review on the Scorpaena plumieri fish venom and its bioactive compounds. Issue 1 (December 2016) - Campos, Fabiana; Menezes, Thiago; Malacarne, Pedro; Costa, Fábio; Naumann, Gustavo; Gomes, Helena; Figueiredo, Suely
Abstract The most poisonous fish species found along the Brazilian coast is the spotted scorpionfishScorpaena plumieri . Though hardly ever life-threatening to humans, envenomation byS. plumieri can be quite hazardous, provoking extreme pain and imposing significant socioeconomic costs, as the victims may require days to weeks to recover from their injuries. In this review we will walk the reader through the biological features that distinguish this species as well as the current epidemiological knowledge related to the envenomation and its consequences. But above all, we will discuss the challenges involved in the biochemical characterization of theS. plumieri venom and its compounds, focusing then on the successful isolation and pharmacological analysis of some of the bioactive molecules responsible for the effects observed upon envenomation as well as on experimental models. Despite the achievement of considerable progress, much remains to be done, particularly in relation to the non-proteinaceous components of the venom. Therefore, further studies are necessary in order to provide a more complete picture of the venom's chemical composition and physiological effects. Given that fish venoms remain considerably less studied when compared to terrestrial venoms, the exploration of their full potential opens a myriad of possibilities for the development of new drug leads and tools for elucidating the complex physiological processes.